Comparison Study Of Measurement Results Between Rain Gauge 7052.0100 and Optical Rain Gauge 815 at Lapan Kototabang - Ulfa Fadhilah; - Asrizal; - Yohandri; - Syafriani; Ridho Pratama (PILLAR OF PHYSICS, 2022)
In general, the population in Indonesia is a farmer. This causes farmers to need information about the weather to carry out agricultural activities. One way to obtain information about the weather is to use the Rain Gauge instrument. In this study, the Rain Gauge instrument at LAPAN Kototabang from 2020 to 2021 was compared with the Optical Rain Gauge instrument. This research uses descriptive research with secondary data in the form of rainfall intensity data that has been measured on the Rain Gauge and Optical Rain Gauge from LAPAN Kototabang. This research was conducted to analyze the output data from the Rain Gauge and Optical Rain Gauge in the form of rainfall intensity, rainfall accumulation, and time. From the data analysis, two results can be stated from this research. First, the analysis of the rainfall parameter data that has been processed shows that the rainfall in Kototabang in January - October 2020 and 2021 has a high rainfall value. This causes the intensity of rainfall in Kototabang to be categorized as heavy rain. The two accumulations of rainfall in 2020 and 2021 in the Kototabang area are 497.031 mm and 0.602 mm using the Rain Gauge. While the measurement using Optical Rain Gauge rainfall intensity is 0.207 mm and 0.221 mm. This proves that the intensity of rainfall in 2020 is greater than the intensity of rainfall in 2021.